Moral reasoning among Dutch community pharmacists: testing the applicability of the Australian Professional Ethics in Pharmacy test. - Kruijtbosch, M.; Göttgens-Jansen, W.; Floor-Schreudering, A.; van Leeuwen, E.; Bouvy, M. L. (International Journal of Clinical Pharmacy, 2019)
Background Moral reasoning competency is essential in healthcare practice, especially in situations of moral dilemmas when a professional has to choose a morally justifiable action among several suboptimal action options. The Australian Professional Ethics in Pharmacy test (PEP test) measures moral reasoning among pharmacists. In Australia three levels of moral reasoning (schemas) were measured (1) business orientation (2) rules and regulations, and (3) patient rights (i.e. most advanced schema). Objective To test the applicability of the PEP test to pharmacists working in the Netherlands. Setting Dutch community pharmacy. Methods The PEP test consists of 36 statements (items) accompanying 3 moral dilemma scenarios. It was translated into Dutch and completed by 390 pharmacists. Principle component analysis (PCA) was used to investigate construct validity and Cronbach's Alpha was used to indicate internal consistency of the Dutch version of the PEP test. The eligible grouped statements and perceived possible moral reasoning schemas were compared to the Australian findings. Main outcome measure Moral reasoning schemas. Results The PCA analysis resulted in 3 components (i.e. possible moral reasoning schemas) that together accounted 27% variance in the data. The statements that represented the moral reasoning schemas 'business orientation' and 'rules and regulations' were somewhat similar when comparing these with the statements that represented these schemas in the PEP test study. The most advanced moral reasoning schema identified in Dutch pharmacists contained different statements compared to the statements that represented that schema among Australian pharmacists. This schema was labelled 'professional ethics'. Conclusion The PEP test needs further adaptation to the Dutch pharmacy practice context: especially the statements that should reflect the most advanced moral reasoning schema, need more accurate representations of professional pharmacy ethics that guide pharmacists in the Netherlands. Moral reasoning tests for a specific professional setting or country should be developed and adapted by experts who share the same professional values and practice as the respondents.